Aktivitas Seksual Lansia - Desy Purnamasari; Margono; Nanik Setiyawati (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2014)
Background: According to UNFPA research and BKKBN in Yogyakarta in 1999, it discovered that woman respondent in the range of age 59 years old with different background, said that they won’t make sex with their husband and let them to have affair.Objective: This research was taken to describe the sexual activity for the overage in Saragan, Pandowoharjo, Sleman.Methode: It used qualitative method with the kind of research was descriptive research. It took place in Saragan, Pandowoharjo Sleman on May until June 2014. The research subject was the old people of the range of age was up to 60 years old. The informan in this research are 7 old people, 4 women and 3 men. The researcher took research based on behavior, attitude, subjevtive norm and the intention of the old people about sexual activity. The data was collected by using in-depth interview.Result: The result of the research showed that the woman respondent were still doing kiss, hug, and have sex. And all the man respondent hadn’t done sex anymore. Half of the woman respondents had positive attitude about sexual activity but all of the man respondents have negative attitude to activity sexual. All of the respondent point of view were influenced by their couple, family, myth about the tumors, and workshop. All of women respondent had the intention of making sex and the man respondent hadn’t it.Conclusion: All the woman respondents were still doing kiss, hug, and have sex. And the man respondent hadn’t done sexual activity anymore.Keywords: Sexual behavior, attitudes toward sexual activity, intentions, overage